THE EFFECT OF KNOWLEDGE SHARING DIMENSIONS ON PERCEIVED FIRM INNOVATION: AN EMPIRICAL RESEARCH ON IT COMPANIES (Third Sector Social Economic Review, 2020)
The purpose of this study is to test the effect of knowledge sharing and dimensions of individual, organizational and technological factors on the firm's innovation capability in information Technologies (IT) companies. Especially in IT companies that are dependent on high technology, knowledge sharing and creating an innovative-oriented organizational climate are much more important for these organizations operating in a dynamic environment. In this context, a survey is conducted on 166 people working in 120 IT companies operating in four big technoparks (Gazi, METU, Hacettepe and Cyberpark) within Ankara. The results obtained show that individual, organizational and technological factors significantly affect the variables of knowledge donating and knowledge collecting. Also, it is determined that the variables of knowledge donating and knowledge collecting significantly affect the perceived firm innovativeness level. These findings reveal that knowledge sharing behaviour and activities are a facilitating factor in improving the firm innovation capability, especially in sectors with high technology dependence.
Keywords: IT companies; Knowledge sharing; Firm innovation capability; Organizational innovation.